2018
DOI: 10.30802/aalas-jaalas-17-000134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serial Blood Collection by Facial Vein and Retrobulbar Methods in C57BL/6 Mice

Abstract: Many biomedical research protocols for mouse models involve serial blood collection and analysis. Two common techniques for serial blood collection in this species are the retrobulbar (RB, also called retroorbital) and facial vein (FV) methods. However, previous studies comparing these methods typically evaluated collection at a maximum of 2 time points. Here we compared hematologic values, adverse clinical effects, and histopathologic lesions in mice bled either once or serially (6 times) by using the FV or R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In a retrospective study [26] with facial vein sampling performed serially, a mortality rate of 4/214 mice was observed (≈2%). Frolich et al 2018 [29] reported a substantially higher mortality rate of (4/12, 33%) when mice were serially sampled by the facial vein route. There was no associated mortality with the single-sample facial vein route or retrobulbar routes, or serial retrobulbar sampling [29].…”
Section: Mortalitymentioning
confidence: 99%
See 4 more Smart Citations
“…In a retrospective study [26] with facial vein sampling performed serially, a mortality rate of 4/214 mice was observed (≈2%). Frolich et al 2018 [29] reported a substantially higher mortality rate of (4/12, 33%) when mice were serially sampled by the facial vein route. There was no associated mortality with the single-sample facial vein route or retrobulbar routes, or serial retrobulbar sampling [29].…”
Section: Mortalitymentioning
confidence: 99%
“…The major physiological measures investigated were those reflecting fear or arousal, via the hypothalamic-pituitary-adrenal (HPA) axis response [2,[7][8][9][10][11]13,24,31,35,36,38] and the associated release of stored glucose [1,22,23,25,29,32,34,37]. Stress almost invariably activates the HPA axis, which, via a sequence of steps, leads to glucocorticoid production-the principle rodent glucocorticoid being corticosterone.…”
Section: Physiological Measuresmentioning
confidence: 99%
See 3 more Smart Citations